More of the Same?: Influences on source use and source affiliation diversity in for-profit and nonprofit news organizational content. (25th January 2019) - Boehmer, Jan; Carpenter, Serena; Fico, Frederick
Abstract : Sources are an indicator of news quality. They cue readers to the extent that journalists are invested in reporting a topic. Moreover, a diversity of sources may help readers reach more informed decisions. This study investigates the amount and diversity of sources nonprofit and for-profit news organizations use and what factors affect sourcing behaviors. Results indicate that nonprofit organizations use more, but not more diverse sources. In addition, journalists more often covering conflict and enacting roles beyond dissemination are likely to use more and more diverse sources. Increased workload, though, predicts stories with fewer and less-diverse sources.